Establishment Of Unique Rehabilitation Protocol and Stroke Specific Gymnasium for Post Stroke Individuals - Kanase, Suraj; Jadhav, Piyusha; Jadhav, Neharika (Journal of Neonatal Surgery, 2025)
Background: Stroke is a leading cause of disability worldwide, with individuals aged 30-40 years being increasingly affected. Effective rehabilitation protocols and specialized gyms can significantly improve outcomes in post-stroke individuals. Objective: To establish a unique rehab protocol and stroke-specific gym for post-stroke individuals aged 30-40 years and evaluate its effectiveness using the Functional Independence Measure (FIM) and Barthel Index. Methods: This study recruited 20 post-stroke individuals aged 30-40 years. Participants underwent a 6-week rehab protocol, which included specialized exercises and activities tailored to their needs. Outcome measures were assessed using the FIM and Barthel Index at baseline, post-intervention, and follow-up. Results: This study of 20 post-stroke individuals (mean age 35.5 ± 3.2 years) showed significant improvements in functional independence and outcomes using a unique rehab protocol and stroke-specific gym. FIM scores improved from 64.5 to 90.5 and Barthel Index scores improved from 55.2 to 80.2. Conclusion: This study demonstrates the effectiveness of a unique rehab protocol and stroke-specific gym in improving functional independence and outcomes in post-stroke individuals aged 30-40 years. Future studies can build upon these findings to develop more targeted and effective rehabilitation programs